The Power Threat Meaning Framework: a qualitative study of depression in adolescents and young adults - Ekbäck, Erik; Rådmark, Lina; Molin, Jenny; Strömbäck, Maria; Midgley, Nick; Henje, Eva (Frontiers in Psychiatry, 2024)
Introduction Depression constitutes one of our largest global health concerns and current treatment strategies lack convincing evidence of effectiveness in youth. We suggest that this is partly due to inherent limitations of the present diagnostic paradigm that may group fundamentally different conditions together without sufficient consideration of etiology, developmental aspects, or context. Alternatives that complement the diagnostic system are available yet understudied. The Power Threat and Meaning Framework (PTMF) is one option, developed for explanatory and practical purposes. While based on scientific evidence, empirical research on the framework itself is still lacking. This qualitative study was performed to explore the experiences of adolescents and young adults with depression from the perspective of the PTMF. Methods We conducted semi-structured interviews with 11 Swedish individuals aged 15– 22 years, mainly female, currently enrolled in a clinical trial for major depressive disorder. Interviews were transcribed verbatim and analyzed with framework analysis informed by the PTMF. Results A complex multitude of adversities preceding the onset of depression was described, with a rich variety of effects, interpretations, and reactions. In total, 17 themes were identified in the four dimensions of the PTMF, highlighting the explanatory power of the framework in this context. Not all participants were able to formulate coherent narratives. Discussion The PTMF provides a framework for understanding the complexities, common themes, and lived experiences of young individuals with depression. This may be essential for the development of new interventions with increased precision and effectiveness in the young.